2022
DOI: 10.3390/fermentation8110633
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Reactive Extraction with and without 1-Octanol as Phase Modifier: Experimental and Modeling

Abstract: Gallic acid (GA) is a naturally occurring phenolic acid that can be found in the leaves, roots, flowers, or stems of a wide variety of plant species. It has a broad range of uses in the food and pharmaceutical industries. The objective of this research is to investigate the GA reactive extraction process employing dichloromethane and n-heptane as solvents, 1-octanol as a phase-modifier, and Amberlite LA-2 as an amine extractant dissolved in the organic phase. The separation yield and distribution coefficient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The main factors investigated in the reactive extraction of muconic acid were pH, temperature, extractant concentration, and time [49][50][51][52]. It was demonstrated that the pH of the aqueous phase has a significant impact on carboxylic acid reactive extraction [15][16][17][18][19]. In reactive extraction, MA can interact with the extractant in one of two ways: (I) by hydrogen-bonding with the undissociated acid molecule, or (II) by the formation of ion pairs when MA is dissociated (pH > pKa), Figure 5.…”
Section: Reactive Extraction Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors investigated in the reactive extraction of muconic acid were pH, temperature, extractant concentration, and time [49][50][51][52]. It was demonstrated that the pH of the aqueous phase has a significant impact on carboxylic acid reactive extraction [15][16][17][18][19]. In reactive extraction, MA can interact with the extractant in one of two ways: (I) by hydrogen-bonding with the undissociated acid molecule, or (II) by the formation of ion pairs when MA is dissociated (pH > pKa), Figure 5.…”
Section: Reactive Extraction Influencing Factorsmentioning
confidence: 99%
“…The reactive extraction approach has recently drawn more attention as a viable and efficient way to remove carboxylic acids from the fermentation broth and is frequently carried out utilizing a combination of extractants and solvents [13][14][15][16][17][18][19]. The classic systems, which include amines or organophosphorus extractants dissolved in organic solvents, have been improved in a substantial number of research articles over the past few decades in terms of sustainability and efficiency [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive extraction is based on a reaction between an extractant (dissolved in the organic solvent) and the target solute (e.g., carboxylic acids dissolved in the aqueous phase). Several carboxylic acids (gallic acid [14,15], keto-gluconic acid [16], pseudo-monic acid [17], lactic acid [18]), and vitamins (vitamin C [19], vitamin B5 [20]) have been successfully separated through this method at laboratory scale. For sustainability of this process, finding a selective, affordable, and effective extractant and diluent system based on maximal efficiency and minimal toxicity and determining the ideal implementation circumstances are the key challenges in using reactive extraction for the recovery of organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…For the scale-up application of reactive extraction, rigorous modelling and optimization of laboratory-scale studies are essential and different models can be applied [15][16][17]. ANNs are inspired by the biological brain, and GWO is inspired by the grey wolf's social hierarchy and hunting mechanism [26].…”
Section: Introductionmentioning
confidence: 99%